Weeding and disposal in Academic Labraries: mapping of scientific production - Silva, Márcia Regina; Castro Filho, Cláudio Marcondes; Quirino, Paula Oliveira (Faculdade de Filosofia e Ciências, 2013)
The aim of this study is to raise and discuss the literature on weeding and disposal in academic libraries. A survey of documents in databases of national and international scientific articles that address this issue. Items recovered on disposal and weeding were filtered and separated into four categories, namely: physical space, the current collection, collection development and other aspects. The results indicate that the process of weeding and disposal is not much explored in the literature, both nationally and internationally, in addition, there are indications that not all libraries that care to follow training policies and collection development statements.